Implementation of a monitoring add-on for oxygen-15 labelled water administration system in PET/CT - Tirkkonen, Jussi (My University, 2025)
Positron emission tomography (PET) is a highly advanced non-invasive imaging technology that allows the acquisition of detailed internal images. PET imaging is applied in multiple fields such as clinical oncology and cardiac perfusion studies. PET employs radioactively labelled components known as radiotracers, to act as biological labels in imaging procedures. Radiotracers are administered to the patient prior to image acquisition. Due to the nuclear instability of these radiotracers, they are considered as radiotoxic substances, and the administration process needs to be monitored rigorously to ensure the safety of patients and operation staff. One of the most significant radiotracers in cardiovascular imaging is oxygen-15 labelled water [15O-H2O] also known as radiowater. It is used in clinical and research applications throughout the world. The gold standard for radiowater production instruments is the Hidex Radiowater Generator (RWG). The current system, however, has limitations that Turku PET Centre together with the manufacturer Hidex Oy is aiming to overcome with the implementation of a monitoring unit that can be installed parallel to an existing RWG setup. This implementation is a part of a larger project titled WASP, (Radio)Water Administration Standardisation Project. In this research project, the said add-on was installed to three existing RWG systems and standard procedure runs were performed according to Turku PET Centre protocol. A total of 29 measurements were completed and recorded, from which the stability and repeatability of the add-on was evaluated. Evaluation was carried out by comparing both individual and total data regarding the pressure and component flow similarity and the bolus curve characteristics. In this project the implementation was successful, and the system was found to be stable regarding all monitored factors. Possible instability within the systems was justified as instrumentation variance, unrelated to the add-on. The add-on was deemed interchangeable within different RWG systems.
Keywords: PET imaging, Radiotracer, Oxygen-15, Medical Instrumentation